Publication patterns and coauthorship in the Journal of Corporate Finance - Andrikopoulos, Andreas; Trichas, Georgios (Journal of Corporate Finance, 2018)
In this article, we explore publication patterns in the Journal of Corporate Finance and discuss scientometric results from 1994 to 2017. We document evidence on the number and size of published papers, collaborative research in terms of coauthorship, editorial board characteristics, and citations as approximations of scientific impact. We identify the most prolific individuals and institutions and discuss how published research has exhibited an increasing number of authors per paper (2.38 on average), how the percentage of USA-based affiliations is gradually decreasing, and how 10.32% of published papers have been written by a member of the editorial board. In an attempt to map the social structure of collaboration in the Journal of Corporate Finance, we studied the social network of coauthors and found that the most prolific authors and institutions are also among the most central ones. We also discovered that the network of coauthorship spreads across 470 connected groups of nodes, the largest of which spans 24.63% of the network.